Spectrums of Co-Creation: An Analysis of the Co-Creation Process in the Development of the Irish National Opera's Community VR Opera, Out of the Ordinary/As an nGnách. - Wandel-Brannigan, Caoimhe; Matamala, Anna (Journal of Arts Management, Law & Society, 2024)
This article examines a hybrid co-creation process facilitated by the Irish National Opera as part of the Europe-wide Traction project. It explores the digital and physical spaces that enabled the creation of a virtual reality community opera, at the height of the Covid-19 pandemic. It triangulates qualitative and quantitative data collected from evaluation instruments including questionnaires, evaluation logs and semi-structured interviews with professional and nonprofessional artists across a two-year period. Key findings indicate that the incorporation of digital technologies in co-creation can enhance a dynamic, collaborative, nonhierarchical process and environment for both professional and nonprofessional artists, though its limitations are also exposed. The project's value is largely derived through its democratic and experimental underpinnings, though the potential for asymmetrical power dynamics is observed. Finally, it highlights that authentically engaging communities in an artistic process necessitates that they recognize themselves within the very structures of the project itself.